Assessment of Heavy Metals on Occupationally Exposed Workers from Hair Analysis - E. Damastuti; N. Adventini; W.Y.N. Syahfitri; S. Kurniawati; D.D. Lestiani; M. Santoso (Atom Indonesia, 2017)
The use of human hair as a tool in assessing changes and abnormalities in human bodies has been increasing for last decades since it may reflect the health status or environmental condition of habitation or working place of individuals as well as population groups. Compared to other body tissue or fluids, hair provides an ease of elemental analysis especially in reflecting the long-term exposure. This research was conducted to determine the elemental content especially heavy metals, since they are bioaccumulated in human body organs and impact human health, in hair of workshop workers and traffic services officers as exposed groups and its comparison with control group and references data for assessing of occupational exposure. Thirty-five automotive workshop workers and 32 traffic services officers’ hair specimens were collected in Bandung, while hair specimens of the control group were collected from 43 healthy individuals. The elemental concentrations in hair specimen were analyzed using neutron activation analysis (NAA) for mercury and chromium, and atomic absorption spectrometry (AAS) for lead and arsenic.  The accuracy of the method was evaluated using GBW 07601 human hair certified reference material (CRM) and it was found to give good results in accordance with the certificate values. It was found that chromium, lead, and arsenic hair concentration in exposed groups (0.88, 10.7, and 0.051 mg/kg, respectively) were higher than in control group (0.27, 4.52, and 0.045 mg/kg, respectively), while mercury hair concentration of traffic services officers were higher than control group but mercury hair concentration of automotive workshop workers were lower than in control group (1.41 mg/kg). The t-test statistical results shown that mercury concentrations in one exposed group did not differ significantly from the control, but other exposed groups showed otherwise. The level of mercury in hair is strongly attributed not only to environmental exposure, but also to lifestyle and dietary habits, while t-test statistical results ofchromiumand lead differ significantly with p value < 0.05. These results indicate that heavy metal hair concentrations were well quantified to show the abnormalities of elemental concentration in human hair for evaluating the occupational exposure.